Western Monarch Population Plummets: Status, Probable Causes, and Recommended Conservation Actions - Pelton, Emma M.; Schultz, Cheryl B.; Jepsen, Sarina J.; Black, Scott Hoffman; Crone, Elizabeth E. (Frontiers in Ecology and Evolution, 2019)
Western monarch butterflies dropped by ~97% of their average historic abundance between the 1980s and mid-2010s. In winter 2018-2019, the population plummeted even farther, to fewer than 30,000 monarchs, which represents a single year drop of 86% and a drop of >99% since the 1980s. The population may now be hovering at its quasi-extinction threshold. In this Perspectives piece, we: 1) Place the current status in context, 2) Recap probable causes of declines, 3) Highlight the most likely window during the annual life cycle that the population declined, and 4) Recommend steps that the public, policy makers, and land managers can take to recover western monarchs. The available studies reinforce the hypotheses that overwintering habitat loss and loss of central California breeding habitat, as well as pesticide use, are likely important contributors to the western monarch’s long term decline. The most limiting part of the migratory cycle appears to be concentrated during the overwintering stage and/or in early spring. If western monarchs are in fact entering an extinction vortex, they need extraordinary efforts—focused on the most vulnerable periods of the annual cycle— to save the migration. Critical short-term conservation priorities include 1) Protect, manage and restore overwintering habitat, 2) Restore breeding and migratory habitat in California, 3) Protect monarchs and their habitat from pesticides, 4) Protect, manage, and restore summer breeding and fall migration monarch habitat throughout the western monarch’s range, and 5) Fill research gaps to inform western monarch recovery strategies.